Television Journalists' Perceptions of Agricultural Stories and Sources in Texas - Kori Barr; Erica Irlbeck; Courtney Meyers; Todd Chambers (Journal of Applied Communications, 2011)
Agricultural organizations often struggle to have their messages heard on television news. Stories about agriculture often contain interview sources that are sometimes not equipped with the first hand knowledge to answer questions about the subject, leaving agricultural organizations wondering why their experts were not interviewed. The purpose of this study was to explore factors that influence the selection of stories and interview sources for television stories in an effort to improve agricultural organizations’ presence in television news. Fifteen participants from four Texas television markets were interviewed. The data indicate that newsworthiness of agricultural stories depended on market size, with larger markets airing agricultural stories only when highly newsworthy—usually some sort of crisis— events occurred, and smaller markets were more willing to run agricultural stories that could include seasonal stories (harvest, planting, etc.), agricultural innovations, weather’s impact on a crop, or agriculture’s impact on a community. In addition, although opinions on the credibility of certain agricultural sources varied from person to person, governmental sources were considered to be credible in general, with commodity groups, corporations, and interest groups being perceived as a bit less credible. Conclusions were drawn that familiarity and acquaintanceship play a large role in the selection of sources by reporters, and the researchers recommend that agricultural organizations strive to cultivate these relationships to allow for better information transfer.
Keywords: television reporters; agriculture; gatekeeping theory; source credibility theory